2019
DOI: 10.1159/000495245
|View full text |Cite
|
Sign up to set email alerts
|

Successful Endoscopic Management of Double Iatrogenic Perforations Induced by Endoscopic Retrograde Cholangiopancreatography and Computed Tomography-Guided Colon Drainage

Abstract: Endoscopic retrograde cholangiopancreatography (ERCP) is a high-risk procedure with a significantly high rate of complications, such as pancreatitis, bleeding, perforation, and infection. Pancreatitis is the most common post-ERCP complication with an incidence of approximately 3.5%. Although perforation is a rare complication with an incidence of 0.1–0.6%, it may be associated with a high rate of mortality of 1.0–1.5%. Here, we report a rare case of ERCP-induced double iatrogenic perforations in the duodenum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…A pigtail catheter is a universal drain used to remove fluids or abscesses from organs, ducts, or body cavities. Some of the reported complications of pigtail catheter insertion include lung penetration during pleural effusion removal and entrapment of the catheter in the tricuspid valve leaflet during heart catheterization [8,14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pigtail catheter is a universal drain used to remove fluids or abscesses from organs, ducts, or body cavities. Some of the reported complications of pigtail catheter insertion include lung penetration during pleural effusion removal and entrapment of the catheter in the tricuspid valve leaflet during heart catheterization [8,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Infrequent complications have been discussed in studies regarding pigtail catheter found on computerized tomography (CT) scan following a procedure. Pigtail plastic stents are used to remove the intra-abdominal drainage during procedures such as endoscopic retrograde cholangiopancreatography (ERCP) [8].…”
Section: Introductionmentioning
confidence: 99%